Individual and parentage testing in horses by pcr methodology - Mehmet Nizamlıoğlu; Ercan Kurar; Ercan; Zafer Bulut; Şeref İnal; Ferudun Erzurum (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to develop and test a microsatellite panel for parentage analysis in horses. Materials and Methods: A total of 189 blood samples were collected from four different horse breeds in Turkey. We selected five horse microsatellite loci and used to amplify genomic DNA by polymerase chain reaction (PCR). The resulting PCR products were separated on polyacrylamide gels. Allele identification was conducted based on their base-pair size by comparing a size standard. Results: A total of 53 alleles was determined ranging from 9 to 13 at each locus. The observed heterozygosity (Ho) and expected heterozygosity (He) were ranged from 0.496 to 0.880 and from 0.800 to 0.851, respectively. Polymorphism information content (PIC) values were observed between 0.774 and 0.832. Power of exclusion (PE) at each microsatellite locus ranged from 0.619 to 0.702, resulting in a total PE value of 0.99060. Conclusion: These results indicate that this set of microsatellite is useful for horse parentage testing in Turkey. Due to possible high level of inbreeding in some breeds, the use of increased number microsatellite loci will thereby be appropriate for avoiding a false parenting and misidentification.